2013
DOI: 10.1007/s10877-013-9461-6
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed intraoperative fluid therapy guided by stroke volume and its variation in high-risk surgical patients: a prospective randomized multicentre study

Abstract: Perioperative hemodynamic optimisation improves postoperative outcome for patients undergoing high-risk surgery (HRS). In this prospective randomized multicentre study we studied the effects of an individualized, goal-directed fluid management based on continuous stroke volume variation (SVV) and stroke volume (SV) monitoring on postoperative outcomes. 64 patients undergoing HRS were randomized either to a control group (CON, n = 32) or a goal-directed group (GDT, n = 32). In GDT, SVV and SV were continuously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 47 publications
3
113
0
5
Order By: Relevance
“…Moreover, comparable effects of GDT using solely the FloTrac/Vigileo system to its effects using other hemodynamic monitors have been demonstrated, and this therapy has been reported as simple and safe [10] [11]. We also previously reported in a small series (before the present study) that GDT contributes to the standardization of fluid management [13] and a reduction in surgical costs [14].…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, comparable effects of GDT using solely the FloTrac/Vigileo system to its effects using other hemodynamic monitors have been demonstrated, and this therapy has been reported as simple and safe [10] [11]. We also previously reported in a small series (before the present study) that GDT contributes to the standardization of fluid management [13] and a reduction in surgical costs [14].…”
Section: Discussionsupporting
confidence: 59%
“…A goal-directed fluid therapy, which aims to achieve maximal cardiac output and stroke volume while avoiding fluid overload, is associated with reductions in mortality, postoperative complications, and length of hospital stay compared with fluid management guided with traditional physiologic targets [heart rate (HR), blood pressure (BP), central venous pressure, urinary output, arterial oxygenation, and pH] (Pearse et al, 2005;Scheeren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since the start of the trial in May 2012, a number of interesting studies have been published which partially addressed the shortcomings mentioned above [5, 2123]. Two studies demonstrated that the implementation of a goal-directed strategy was cost-effective [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies demonstrated that the implementation of a goal-directed strategy was cost-effective [21, 22]. In addition, two multicenter studies were performed in which a reduction in complications was shown [5, 23]. However, minor complications were included, and the number of patients was rather small in these studies.…”
Section: Introductionmentioning
confidence: 99%